Assessing And Mitigating The Impact Of Fake News In Nigeria - Folayan, Bolu John; Olubunmi Banjo, Bosede; Odenike, Omolaso (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2024)
The high rate fake news - news (presentation) that has been distorted or totally false - in the Nigerian media space is at the moment of concern to communication scholars, journalists, publicists, and political leaders. Like most fake products, fake news is made to look like or to have the characteristics of the original product – magnitude, timeliness, novelty, proximity, etc., thereby having the lethal impact of propaganda. The present study examines the sources, patterns of fake news dissemination, impact of and solutions to fake news in Nigeria. Questionnaires were randomly administered online to 398 heavy users of social media (257 bloggers; 97; regular users of social media who are non-professionals; 37 journalists and 7 others based on their followership ratings. The investigation revealed that most fake news in Nigeria revolve social, entertainment, and religious issues and are reported more often in “text” and “videos” on Facebook, Instagram, and WhatsApp. The main sources of fake news in Nigeria are non-professional journalists and the high rate of fake news has largely been due to the skilful framing by their disseminators, lack of time and skill to fact-check fake news by the audience, and lack of effective enforcement of best journalism practices.